Towards testing a two-Higgs-doublet model with maximal CP symmetry at the LHC: Monte Carlo event generator implementation - Brehmer, Johann; Lendermann, Victor; Maniatis, Markos; Nachtmann, Otto; Schultz-Coulon, Hans-Christian; Stamen, Rainer (The European physical journal. C, Particles and fields, 2013)
A Monte Carlo event generator is implemented for a two-Higgs-doublet model with maximal CP symmetry, the MCPM. The model contains five physical Higgs bosons; the ρ′, behaving similarly to the standard-model Higgs boson, two extra neutral bosons h′ and h″, and a charged pair H±. The special feature of the MCPM is that, concerning the Yukawa couplings, the bosons h′, h″ and H± couple directly only to the second-generation fermions but with strengths given by the third-generation-fermion masses. Our event generator allows the simulation of the Drell-Yan-type production processes of h′, h″ and H± in proton-proton collisions at LHC energies. Also the subsequent leptonic decays of these bosons into the μ+μ−, μ+νμand $μ^{-} \bar{ν}_{μ}$channels are studied as well as the dominant background processes. We estimate the integrated luminosities needed in pp collisions at center-of-mass energies of 8 and 14 TeV for significant observations of the Higgs bosons h′, h″ and H± in these muonic channels.